Factors Affecting Delivery Methods in Severe Preeclampsia Patients at Dr. RSUP. Mohammad Hoesin Palembang January 2018 – December 2019 - Hadrians Kesuma Putra; Adnan Abadi; Dinda Radeta (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: Hypertension in pregnancy (HIP) is the second highest cause of maternal death in Indonesia. Termination of pregnancy in patients with HIP or preeclampsia is the most common treatment to save both the mother and the fetus. There are two methods of delivery that can be done, namely vaginal or abdominal termination (sectio caesaria). Due to the high incidence of severe preeclampsia in Indonesia and the various determinants in choosing a delivery method for severe preeclampsia, the aim of this study is to analyze what factors influenced it in Dr. Mohammad Hoesin Palembang Hospital. Method: This type of study is an analytic observational study with a cross-sectional study design. A total of 210 samples were taken using the simple random sampling technique from the medical records of severe preeclampsia patients who gave birth at Dr. Mohammad Hoesin Palembang Hospital during January 2018 – December 2019 and was analyzed by univariate, bivariate and multivariate analysis with SPSS ver.26. Result: A total of 81 (38.6%) PEB patients underwent vaginal delivery and 129 (61.4%) underwent a caesarean section delivery. From the observations, 67 people (57.3%) were aged 20-34 years, 40 people (78.4%) with a gestational age of 34-36 weeks, 92 people (57.9%) multiparity, 104 people (62, 3%) without a history of hypertension, 86 people (53.4%) without a history of SC, 98 people (84,5%) with a bishop score ≤5, 116 people (59,5%) without PJT, 122 people (61%) without macrosomic fetuses, 108 people (63.5%) without PROM, and 84 people (75%) with complications underwent cesarean delivery. The factors of gestational age (p value = 0.001), history of sectio caesaria (p value = 0.000), bishop score (p value = 0.000), and complications or comorbidities (p value = 0.000) had a significant relationship to the method of delivery for patients with PEB with factors bishop score is the most influencing factor (OR = 10,299). Conclusion: Therefore, gestational age, history of CS, bishop score, and complications or comorbidities are factors that influence the delivery method of PEB patients.